Rozmanitost projevů heteroplazmické mtDNA mutace 8993 T > G ve dvou rodinách - Tesarová, M; Hansíková, H; Hlavatá, A; Klement, P; Houst'ková, H; Houstĕk, J; Zeman, J (Casopis lekaru ceskych, 2002)
BACKGROUND: The most frequent manifestations of heteroplasmic mitochondrial DNA (mtDNA) mutation 8993 T > G are Leigh syndrome or NARP syndrome (Neurogenic Muscle Weakness, Ataxia, and Retinitis Pigmentosa). The authors describe heterogeneity of clinical symptoms and results of biochemical and molecular analyses in seven severely clinically affected children from two unrelated families with heteroplasmic mtDNA mutation 8993 T > G. METHODS AND RESULTS: Seven clinically affected children from two unrelated families were born in term after an uneventful pregnancy. The failure to thrive, psychomotor retardation, hypotonic or spastic quadruparesis, hypertrophic cardiomyopathy, hepatopathy and hyperlactacidaemia developed after birth. Five children died in the first year of life during acute respiratory infection, one girl died at the age of 3 months with sudden death syndrome, only one boy with spastic quadruparesis and severe psychomotor retardation survived to the age of 8 years. Molecular analyses in all investigated children and their clinically non-affected mothers revealed the presence of heteroplasmic mtDNA mutation 8993 T > G. Mutated copies of mtDNA molecules in maternal tissues were in the range of 15-22%. The mutation load in all analysed children's tissues was higher than 90%. CONCLUSIONS: A broad spectrum of clinical symptoms may be observed in families with heteroplasmic mtDNA mutations 8993 T > G. Affected children with a mutation load higher than 90% usually do not survive after infancy. In both investigated families, a profound increase in the levels of heteroplasmy of mtDNA mutation 8993 T > G was observed in two subsequent generations.
Keywords: DNA, Mitochondrial; lidé; retinopathia pigmentosa; Retinitis Pigmentosa; Point Mutation; Infant; Female; dítě; ataxie; Ataxia; Humans; svalová slabost; Leigh Disease; mužské pohlaví; mitochondriální DNA; Syndrome; ženské pohlaví; Muscle Weakness; Male; Leighova nemoc; Child; syndrom; kojenec; bodová mutace